Developed diamond wire sawing technique with high slicing ability for multicrystalline silicon wafers. Issue 15 (17th November 2020) - Wang, Ting-Chun; Yeh, Tsung-Han; Chu, Shao-Yu; Lee, Hsin-Ying; Lee, Ching-Ting
ABSTRACT: In this work, various reciprocating cycle times of 80, 160, 240, and 320 sec in the diamond wire sawing (DWS) process were adjusted to improve the slicing ability in solar industry. During the same slicing time, the long reciprocating cycle time had less velocity inverse points in comparison with the short reciprocating cycle time. Consequently, the total friction force of the slicing wires used in the DWS process with the short reciprocating cycle time was larger than that of the slicing wires used in the DWS process with the long reciprocating cycle time. It was noting that the lower diamond consumption and better slicing ability in the DWS process with a reciprocating cycle time of 320 sec was obtained in comparison with a reciprocating cycle time of 80 sec. However, since the diamond grits with too high slicing strength to collide the Si material, the serious damages were form on the wafer edge. Therefore, the edge chipping increased to 1.63% as the reciprocating cycle time of 320 sec. The highest mass production yield of 94.22% and the lowest edge chipping of 1.23% for the DWS-sliced mc-Si wafers were obtained as the suitable reciprocating cycle time was 240 sec.